Fase Pembentukan Perubahan Seksual Tokoh Utama Film Serial TV Transit Girls Karya Masato Maeda - Dinda Paramitha; Diana Puspitasari; Muammar Kadafi (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2022)
The sexual orientation of homosexuals who are different from heterogeneous groups triggers identity problems in themselves and in social relations. The process that homosexual individuals go through in facing obstacles to gain legitimacy in society affects the development of their identity. This research aims to describe the process of forming sexual identity so that sexual identity can identify sexual roles. This research is a literature study with descriptive qualitative research with data sources from Masato Maeda's Transit Girls film released in 2015 using Vivienne Cass's model of homosexual identity development. As a result, it is show that Sayuri and Yui can reach six stages of homosexual identity development where they feel comfortable and have fully accepted being a lesbian. Through this research it is hoped that it can become a new knowledge about the process of forming a homosexual individual. Where hetero society is still the biggest influence on the process of developing the individual's identity. Regarding the success of becoming someone with a new identity or going back to the old identity as if it depended on it, that identity will also affect their social. Keywords: homosexual identity development; sexual changes; transit girls; Vivienne Cass.